1997
DOI: 10.1159/000189549
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Immunosuppressive Therapy on Lipoprotein(a) and Other Lipoproteins following Renal Transplantation

Abstract: Coronary heart disease (CHD) is more common in patients with chronic renal failure and is a major cause of death after renal transplantation. Elevated serum levels of lipoprotein(a) (Lp(a)) are a known risk factor for CHD in the general population and levels have been reported to be increased in renal transplant recipients. It has been suggested that cyclosporin may elevate Lp(a) levels. We therefore measured the serum concentration of Lp(a) in 50 renal transplant recipients who were receiving cyclosporin alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Our data are consistent with other prospective studies that have shown decreases of Lp(a) after transplantation several months to years post-transplant [24,25,26,27]. Prevalence of Lp(a) >25 mg/dl was 31–37% after 2–10 months post-transplant [28, 29] and >12 mg/dl in approximately 60% of patients 1 year post-transplant [29]. There are several prospective studies looking at the changes in Lp(a) after transplantation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data are consistent with other prospective studies that have shown decreases of Lp(a) after transplantation several months to years post-transplant [24,25,26,27]. Prevalence of Lp(a) >25 mg/dl was 31–37% after 2–10 months post-transplant [28, 29] and >12 mg/dl in approximately 60% of patients 1 year post-transplant [29]. There are several prospective studies looking at the changes in Lp(a) after transplantation.…”
Section: Discussionsupporting
confidence: 92%
“…The same result was not found in all studies [32, 33]. Brown et al [29] found in a cross-sectional study that patients treated with CSA had higher levels when compared to individuals treated with azathioprine and prednisolone (median –32 vs. 18.3 mg/dl). HDL was also higher in the group not taking CSA (1.41 ± 0.4 vs. 1.24 ± 0.39 mmol).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The increased cardiovascular risk profile as a result of cyclosporine is ascribed to both a quantitative increase in LDL particles and an increased oxidizability of the LDL particles (3)(4)(5). Use of cyclosporine is also associated with increased plasma lipoprotein(a) (Lp[a]) (6) and homocysteine levels (7), but these effects are not unequivocal (8). In addition, unfavorable effects on the fibrinolytic system by cyclosporine have been described (9).…”
mentioning
confidence: 99%
“…31 Patients treated with cyclosporine have higher Lp(a) and HDL levels than those treated with azathioprine and prednisolone. 32 Tacrolimus and cyclosporine can cause similar effects on Lp(a). 31 In the present study, changes in all these parameters were comparable between the tacrolimus and cyclosporine groups, and there was no correlation between the percent change of serum creatinine with Lp(a) and homocysteine in transplant recipients.…”
Section: Discussionmentioning
confidence: 99%